The Reconceptualization of Academic Discourse as a Professional Practice in the Digital Age: A Critical Genre Analysis of TED Talks - Compagnone, Antonio (HERMES - Journal of Language and Communication in Business, 2015)
This paper explores how academic discourse is reconceptualized as a professional practice via the web-mediated genre of TED talks (Technology, Entertainment and Design), popularizing speeches delivered by experts in fields that range from the ‘hard’ disciplines to the social sciences and the humanities. More precisely, this study compares two corpora of academic spoken discourse, i.e., a corpus of transcribed TED talks given by academics (TED_ac) and a corpus of university lecture transcripts (MICASE_lect) drawn from the Michigan Corpus of Academic Spoken English (MICASE) to understand how academics’ communicative purposes differ in these two settings. Drawing on the theoretical frameworks of Critical Genre Analysis (Bhatia 2012) and Discourse Analysis (Goffman 1981; Fairclough 1989; Pennycook 1994; De Fina 1995; Benwell/Stokoe 2006; De Fina 2006), the present study sets out to investigate ways in which academics make use of language on the TED stage to achieve their “private intentions” as professionals (Bhatia 2012), e.g., building up their identity as experts as well as promoting their research and scholarship, rather than training a group of novices in their discipline or merely informing mass audiences. To this end, consideration is given to the distribution of first and second person pronouns in the two pragmatic contexts under investigation. Special emphasis is placed on referents and discourse functions of the pronoun we, which is significantly more frequent in TED_ac than in MICASE_lect. Despite its language-centered approach, this study has a marked sociological intent, as it casts light on an instance of academic discourse seen as an example of “professional practice” embedded in the wider context of a “professional culture” (Bhatia 2012).